2019
DOI: 10.1002/bsl.2408
|View full text |Cite
|
Sign up to set email alerts
|

Firearm legislation and statewide suicide rates: The moderating role of household firearm ownership levels

Abstract: Firearm legislation is associated with statewide suicide rates; however, prior research has often relied upon older data and categorical legislative grades while also failing to consider the nuanced role of firearm ownership. Therefore, the robust literature base on legislation and suicide has not directly examined regarding the extent to which the value of legislation hinges upon the rate of firearm ownership in a given state. The current study examined 2015 US statewide firearm legislation strength scores fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Practical capability for suicide is described as the knowledge of, and access to, means for suicide. The important role of access to lethal means in relation to suicide risk is supported by studies which have shown that firearm legislation, particularly more strict firearm legislation, decreases the rate of suicides using firearms, and has no effect on the suicide rate using other means 1 (Anestis et al, 2019;Boor & Bair, 1990;Fleegler et al, 2013;Ludwig & Cook, 2000). Conceptually, the question is whether practical capability correlates with other components of capability for suicide, namely, fearlessness about death and physical pain tolerance.…”
Section: Current Evidencementioning
confidence: 99%
“…Practical capability for suicide is described as the knowledge of, and access to, means for suicide. The important role of access to lethal means in relation to suicide risk is supported by studies which have shown that firearm legislation, particularly more strict firearm legislation, decreases the rate of suicides using firearms, and has no effect on the suicide rate using other means 1 (Anestis et al, 2019;Boor & Bair, 1990;Fleegler et al, 2013;Ludwig & Cook, 2000). Conceptually, the question is whether practical capability correlates with other components of capability for suicide, namely, fearlessness about death and physical pain tolerance.…”
Section: Current Evidencementioning
confidence: 99%
“…Recent studies have begun to examine the independent effects of state-level rearm laws and rearm ownership on rearm-related outcomes. A study showed an additive relationship between them, in which state-level rearm permissiveness and rearm ownership were both associated with a higher rate of mass shootings (24), while another study showed a moderating relationship in which state-level rearm policy strength was inversely associated with suicide rates in states with higher levels of rearm ownership (25).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have begun to examine the independent effects of state-level rearm laws and rearm ownership on rearm-related outcomes. A study showed an additive relationship between them, in which state-level rearm permissiveness and rearm ownership were both associated with a higher rate of mass shootings (29), while another study showed a moderating relationship in which state-level rearm policy strength was inversely associated with suicide rates in states with higher levels of rearm ownership (30).…”
Section: Discussionmentioning
confidence: 99%